Sodium Ion Microscale Electrochemical Energy Storage Device: Present Status and Future Perspective. Issue 1 (23rd October 2020) - Ma, Jiaxin; Zheng, Shuanghao; Das, Pratteek; Lu, Pengfei; Yu, Yan; Wu, Zhong-Shuai
Abstract : Sodium Ion Microbatteries In article number 2000053, Yan Yu, Zhong‐Shuai Wu and co‐workers summarize the recent advances and present status of sodium ion micro‐electrochemical energy storage devices with different reaction mechanisms and device architectures. Such flexible sodium ion micro‐devices with superior modularization and tailorable performance pave a way for integrated wearable and portable electronics devices.